2003
DOI: 10.4049/jimmunol.171.1.447
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Helminth Products on Immune Responsiveness Using a TCR Transgenic Adoptive Transfer System

Abstract: Helminth infections and their products have a potent immunomodulatory effect on the host immune system and can impair immune responses against unrelated Ags. In vitro studies have suggested that the immunomodulation by helminth extracts may be the result of bystander response bias toward a Th2 phenotype and/or an Ag-specific T lymphocyte proliferative hyporesponsiveness. The aim of this study was to determine the role of these potential mechanisms of immunosuppression in vivo. Therefore, using a sensitive mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This concept is consistent with observations in other Th2 induction systems involving allergic (66,67) as well as helminthtriggered responses (53,68), in which decreased rather than increased CD4 T cell function has been noted. The findings reported in this work now link this behavior to down-regulatory signals in the APC compartment itself, which in turn are associated with retarded lymphocyte activation.…”
Section: Discussionsupporting
confidence: 79%
“…This concept is consistent with observations in other Th2 induction systems involving allergic (66,67) as well as helminthtriggered responses (53,68), in which decreased rather than increased CD4 T cell function has been noted. The findings reported in this work now link this behavior to down-regulatory signals in the APC compartment itself, which in turn are associated with retarded lymphocyte activation.…”
Section: Discussionsupporting
confidence: 79%
“…The immune response to the larval muscle stage of T. spiralis is also characterized by a Th2 response, and this is coupled with an intense IL-10 response which is crucial for controlling the accompanying inflammation (5). These two parasites are therefore present and manipulating the immune response for the duration of the study; it would therefore be of interest to determine if parasite products could elicit similar responses, as has been demonstrated both for diabetes and in other systems (1,4,6,7,9,21,48,50).…”
Section: Discussionmentioning
confidence: 99%
“…Helminth parasites are strong inducers of T helper 2 (Th2) cell-associated responses such as eosinophilia, interleukin-4 (IL-4), IL-5, IL-13, and immunoglobulin E (IgE) production (20,29). In addition to the Th2 polarizing response, the induction of regulatory responses is also a common feature of the immune response induced following exposure to parasitic helminth antigens (6,30,49).…”
mentioning
confidence: 99%
“…There is irrefutable evidence that helminth infections can down-regulate immune responsiveness to other types of infection or to unrelated Ag [5][6][7][26][27][28][29]. We have previously shown that Asc or PI have the same ability as a live infection to strongly suppress the immune response and to induce a typical Th2 response (with IL-4 and IL-10 secretion) which is responsible for the suppressive effect [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…However, some helminths are able to persist in their hosts for many years, creating an anti-inflammatory environment favorable to their survival and maintenance. In this context, it has been demonstrated that helminths down-regulate host's immunity to their own Ag and to a large number of unrelated pathogenic agents [5][6][7]. More recently, it has been reported that some helminth infections promote the generation of T regulatory cells which are responsible in part for the state of immune hyporesponsiveness [8][9][10].…”
Section: Introductionmentioning
confidence: 99%